A framework for data analysis to build business requirements: A case of Barclays Kenya - Kimani, Oscar Ikaba (Strathmore University, 2013)
This study sought to develop a data analysis framework to build business requirements using requests logged by end users of implemented ICT solutions. The study was guided by four objectives that included review of the existing frameworks that align IT to the business. The other objectives are establishment of misalignment between the implemented ICT solutions and business requirements at both detailed and high levels, development of a data analysis framework and validation of the data analysis framework. Self-administered questionnaires supplemented electronic data that was obtained from IT help-desk. The data was cleaned up, edited, coded, tabulated, put into specific categories and frequencies of each category determined by tallying the results. Data was presented in tables, pie charts and bar graphs with textual comments for interpretation. The sample size was 1152 elements and the researcher also analyzed 42 questionnaires that had been distributed randomly to respondents across the business functions. The research findings identified several gaps in the implemented ICT solutions. Users had reported many cases of application errors, outages and other issues affecting service availability. Network issues were reported raising the issue of reliability of the IT infrastructure. There were issues on duplicated transactions, posting errors, data omissions that impacted data integrity and competency of the personnel. Some users had logged issues on automation for efficiency. However the responsiveness by the IT support teams scored highly with 81% of the respondents indicating satisfactory response of within 24 hours. The research met all the set objectives. Literature review investigated frameworks that give guidance on the support of end users, align IT to the business or provide requirements for implementation of business solution. The research findings identified several gaps affecting availability of applications, data integrity and reliability of IT infrastructure. The framework was developed using inputs, activities and outputs and validated using a different sample from the sample frame that also obtained same result.
A dissertation submitted in partial fulfillment of the requirements for the Masters in Computer based Information Systems
Keywords: data analysis; Business; Barclays Kenya